Super-Critical Fluid: An Overview on Analytical Applications - Kadri, Farhin; Xavier, Gauravi; Patel, Unnati; Prajapati, Prajesh (Current Green Chemistry, 2021)
Super Critical Fluid is the emerging technique that consists of super solvent, which is considered a benefit over many other conventional solvents. The main component utilized in it is Carbon Dioxide [CO2], which possesses dual state properties such as effusion through solid and other dissolving materials like liquid which results in unique applications bidden with no limitations. The varying temperature and pressure are the important parameters optimized and thus enhance its solvent properties. Higher Co-efficient of diffusion, reduction in time, higher compressibility, etc. is some of the major advantages of SCF-CO2 over the conventional solvents. Over and above, it is a green approach and a super solvent. Here we have discussed the multifarious applications of the SCF-CO2 extraction in fields and areas extended, but not limited to, Food, Environmental, Analysis, Metal-Cation Extraction, as well as Extractions, Forensics, Pharmaceuticals, Toxins, and Botanical Samples.
Keywords: Supercritical fluid